Valuing Corporate Innovation Strategies, Tools, and Best Practice From the Energy and Technology Sector (Management for Professionals, 2018)
This book presents tools for valuing and controlling corporate innovation. It combines a well-established theoretical framework with case studies at Siemens that illustrate the practice of valuing and controlling innovation and underline the strong link between theoretical concepts and practical application. Innovation is a key factor determining the success of companies and since corporate innovation consumes large quantities of resources, the issue of how best to distribute these resources among different projects is crucial. For an optimal resource allocation, companies need valuation tools to assess the benefits, costs and risks of competing projects. The energy sector is an example of a market that is strongly driven by innovation, and as such the book describes the processes and the potential of digitalizing product development and outlines the valuation process for a long-term innovation project in this sector - the development of the latest Siemens gas turbine.